2013
DOI: 10.1016/j.socscimed.2012.10.016
|View full text |Cite
|
Sign up to set email alerts
|

The influence of urban design on neighbourhood walking following residential relocation: Longitudinal results from the RESIDE study

Abstract: The design of urban environments has the potential to enhance the health and well-being of residents by impacting social determinants of health including access to public transport, green space and local amenities. Commencing in 2003, RESIDE is a longitudinal natural experiment examining the impact of urban planning on active living in metropolitan Perth, Western Australia. Participants building homes in new housing developments were surveyed before relocation (n = 1813; 34·6% recruitment rate); and approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
212
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 268 publications
(242 citation statements)
references
References 54 publications
17
212
1
5
Order By: Relevance
“…Similar findings from a study based on a sample of 279 Irish adults found that residents living in walkable neighborhoods were more likely to know their neighbors, trust others, and be socially engaged compared with those living in car-oriented suburbs [49]. In addition to previous studies that are mostly cross-sectional, a few longitudinal studies also showed the substantial effects of walkable neighborhoods on social capital [50][51][52][53]. For example, a U.S. longitudinal study examined the impact of moving to a walkable neighborhood, Mueller, Austin, TX, on residents' social interactions and cohesion [54].…”
Section: Walkable Neighborhood Amenitiessupporting
confidence: 54%
“…Similar findings from a study based on a sample of 279 Irish adults found that residents living in walkable neighborhoods were more likely to know their neighbors, trust others, and be socially engaged compared with those living in car-oriented suburbs [49]. In addition to previous studies that are mostly cross-sectional, a few longitudinal studies also showed the substantial effects of walkable neighborhoods on social capital [50][51][52][53]. For example, a U.S. longitudinal study examined the impact of moving to a walkable neighborhood, Mueller, Austin, TX, on residents' social interactions and cohesion [54].…”
Section: Walkable Neighborhood Amenitiessupporting
confidence: 54%
“…37 Natural experiments help evaluate legislation to create safe routes to school; 38,39 implementation of cycling infrastructure, 40 sub-division design codes, 41 or walking infrastructure; 37 and park renovations. 42 The UK Medical Research Council has published guidelines for designing natural experiments, 43 and the US National Cancer Institute has called for obesity policy research that includes natural experiments.…”
Section: Evaluate Policy Reform Through Natural Experimentsmentioning
confidence: 99%
“…• detect small effects over time; 41,45 • incorporate policy-specific measures; 46,47 and • monitor implementation to learn what is needed to affect health outcomes. 47 Importantly, natural experiments are more likely to influence policy and practice when undertaken from the outset in partnership with policymakers and practitioners.…”
Section: Evaluate Policy Reform Through Natural Experimentsmentioning
confidence: 99%
“…For instance, Frank et al [103] found that residents of the mixed land-use neighbourhoods walk, bike and transit 2-3 times more and drive almost 60% less compared to those living in more sprawled and automobile-oriented areas. A study by Giles-Corti et al [104] indicated that overall health of residents improved if they moved from dispersed to more compact, walkable neighbourhoods. Sarkar et al [105] found that there is positive association between healthy weight and walkability; and therefore, higher residential density has beneficial effects on accumulated physical activity.…”
Section: Cba Resultsmentioning
confidence: 99%